On Some Scientific Results of Abid-Waheed Graph (AW7r) - Abid Mehboob; Muhammad Waheed Rasheed; Iqra Hanif (Utilitas Mathematica, 2022)
Graphs are the representation of data in pictorial form. The use of graph theory is increasing day by day.